Persistent and transient olfactory deficits in COVID-19 are associated to inflammation and zinc homeostasis - Lupi, Lorenzo; Bordin, Anna; Sales, Gabriele; Colaianni, Davide; Vitiello, Adriana; Biscontin, Alberto; Reale, Alberto; Garzino-Demo, Alfredo; Antonini, Angelo; Ottaviano, Giancarlo; Mucignat, Carla; Parolin, Cristina; et al. (Frontiers in Immunology, 2023)
The Coronavirus Disease 2019 (COVID-19) is mainly a respiratory syndrome that can affect multiple organ systems, causing a variety of symptoms. Among the most common and characteristic symptoms are deficits in smell and taste perception, which may last for weeks/months after COVID-19 diagnosis owing to mechanisms that are not fully elucidated. In order to identify the determinants of olfactory symptom persistence, we obtained olfactory mucosa (OM) from 21 subjects, grouped according to clinical criteria: i) with persistent olfactory symptoms; ii) with transient olfactory symptoms; iii) without olfactory symptoms; and iv) non-COVID-19 controls. Cells from the olfactory mucosa were harvested for transcriptome analyses. RNA-Seq assays showed that gene expression levels are altered for a long time after infection. The expression profile of micro RNAs appeared significantly altered after infection, but no relationship with olfactory symptoms was found. On the other hand, patients with persistent olfactory deficits displayed increased levels of expression of genes involved in the inflammatory response and zinc homeostasis, suggesting an association with persistent or transient olfactory deficits in individuals who experienced SARS-CoV-2 infection.